2019
DOI: 10.1017/s0022215119000550
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic assisted powered adenoidectomy versus conventional adenoidectomy – a randomised controlled trial

Abstract: ObjectiveTo compare endoscopic assisted powered adenoidectomy with conventional curettage adenoidectomy.MethodsA randomised controlled trial was conducted at a tertiary care teaching hospital. Fifty patients with a symptom complex pertaining to adenoid hypertrophy and requiring adenoidectomy were chosen and divided into 2 groups of 25 each. Patients in group A underwent conventional curettage adenoidectomy and those in group B underwent endoscopic assisted powered adenoidectomy. Comparison was based on the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
6
25
0
Order By: Relevance
“…In the current study, mean duration per minute of operation was significantly shorter among conventional curettage method of adenoidectomy group 16.44±2.01 with range from 14 minute to 20 minute, versus 31.67± 2.12 with range from 29 minute to 36 minute of endoscopic assisted powered adenoidectomy group. This came in agreement with Juneja et al (8) who found that the mean operative time was 19.80 minutes (range, 7-28 minutes) in conventional curettage group and 34.08 minutes (range, 15-60 minutes) in endoscopic assisted powered adenoidectomy group. The difference between the two groups was statistically significant (p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, mean duration per minute of operation was significantly shorter among conventional curettage method of adenoidectomy group 16.44±2.01 with range from 14 minute to 20 minute, versus 31.67± 2.12 with range from 29 minute to 36 minute of endoscopic assisted powered adenoidectomy group. This came in agreement with Juneja et al (8) who found that the mean operative time was 19.80 minutes (range, 7-28 minutes) in conventional curettage group and 34.08 minutes (range, 15-60 minutes) in endoscopic assisted powered adenoidectomy group. The difference between the two groups was statistically significant (p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, all patients of both groups represented with nasal obstruction and mouth breathing and CT findings confirmed adenoid enlargement. This came in agreement with Juneja et al (8) , Prakash et al (11) , Somani et al (12) , Datta et al (13) who found that radiographic evaluation revealed enlarged adenoids in 100 % of patients with an adenoidal-nasopharyngeal ratio of equal to or more than 0.7. These findings were corroborated by endoscopic evaluation, which revealed grade III adenoid hypertrophy in 76 % of patients and grade IV in 16%, according to the grading of Clemens et al (14) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…cantly shorter and less hemorrhage was observed using the conventional surgical technique, although the data were not statistically significant. 12 Datta et al and Businco et al similarly reported that surgery time was shorter using the conventional technique. 13,14 However, Stanislaw et al suggested that the surgery time in the microdebrider technique accompanied with endoscopy was shorter.…”
Section: Graphicmentioning
confidence: 97%
“…These approaches have advantages over traditional methods. This issue contains an article, from New Delhi, 2 on the topic of adenoidectomy technique, in which endoscopic-assisted powered adenoidectomy is compared with conventional curettage. The endoscopic method used a curved microdebrider blade inserted through the mouth, with visualisation endoscopically through the nose.…”
mentioning
confidence: 99%